Advances in Plant-Derived Scaffold Proteins - Peng, Congyue Annie; Kozubowski, Lukasz; Marcotte, William R. (Frontiers in Plant Science, 2020)
Scaffold proteins form critical biomatrices that support cell adhesion and proliferation for regenerative medicine and drug screening. The increasing demand for such applications urges solutions for cost effective and sustainable supplies of hypoallergenic and biocompatible scaffold proteins. Here, we summarize recent efforts in obtaining plant-derived biosynthetic spider silk analogue and the extracellular matrix protein, collagen. Both proteins are composed of a large number of tandem block repeats, which makes production in bacterial hosts challenging. Furthermore, post-translational modification of collagen is essential for its function which requires co-transformation of multiple copies of human prolyl 4-hydroxylase. We discuss our perspectives on how the GAANTRY system could potentially assist the production of native-sized spider dragline silk proteins and prolyl hydroxylated collagen. The potential of recombinant scaffold proteins in drug delivery and drug discovery is also addressed.